2008
DOI: 10.1242/dev.016253
|View full text |Cite
|
Sign up to set email alerts
|

Lgl and its phosphorylation by aPKC regulate oocyte polarity formation inDrosophila

Abstract: Specification of the anteroposterior (AP) axis in Drosophila oocytes requires proper organization of the microtubule and actin cytoskeleton. The establishment and regulation of cytoskeletal polarity remain poorly understood, however. Here, we show important roles for the tumor suppressor Lethal (2) giant larvae (Lgl) and atypical protein kinase C (aPKC) in regulating microtubule polarity and setting up the AP axis of the oocyte. Lgl in the germline cells regulates the localization of axis-specifying morphogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 48 publications
3
80
1
Order By: Relevance
“…Recent studies have shown that Lgl is involved in the polarization of the A-P axis in the Drosophila oocyte (Doerflinger et al, 2010;Fichelson et al, 2010;Li et al, 2008;Tian and Deng, 2008). In the early oocyte, Lgl is required for the proper posterior translocation of cell fate determinants as well as the centrosomes (Fichelson et al, 2010;Tian and Deng, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that Lgl is involved in the polarization of the A-P axis in the Drosophila oocyte (Doerflinger et al, 2010;Fichelson et al, 2010;Li et al, 2008;Tian and Deng, 2008). In the early oocyte, Lgl is required for the proper posterior translocation of cell fate determinants as well as the centrosomes (Fichelson et al, 2010;Tian and Deng, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…10,18,19,[22][23][24][25][26] We and others have shown that lgl/dlg/scrib are required for a number of developmental controls during oogenesis. 10,[18][19][20]22,23,[27][28][29][30][31][32][33][34][35][36] In particular, we have identified Lgl as an essential regulator in PFC specification and differentiation, and a role of dlg/scrib in both anterior and posterior patterning of the follicular epithelium. 32,37 In this paper, we show that lgl genetically interacts with dlg/scrib in PFC fate induction, suggesting a common regulatory pathway in this process.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the physiological function of aPKC in Hh signaling further, we used mitotic recombination to generate clones homozygous for aPKC K06403 , a strong allele of aPKC (35). We found that in aPKC mutant cells, Smo accumulated in apical membrane of wing disc ( Fig.…”
mentioning
confidence: 99%